Comment on: Susceptibility Breakpoints and Target Values for Therapeutic Drug Monitoring of Voriconazole and Aspergillus Fumigatus in an in Vitro Pharmacokinetic/Pharmacodynamic Model - Denning, David W.; Ghnan, Nesrin; Kwizera, Richard; Osmanov, Ali (Journal of Antimicrobial Chemotherapy, 2015)
Siopi et al.1 are to be congratulated on a superb paper with convincing results using a combination of resistant isolates and sophisticated pharmacodynamic modelling to demonstrate the strong relationship between voriconazole serum concentrations and outcome. Three different MIC determinations yielded similar although numerically slightly different results. The authors propose slightly different breakpoints for resistance using the EUCAST method and breakpoints can now be set for Aspergillus fumigatus for the other two methods.
Keywords: fumigatus, fungicidal, paediatrics